Family support in postpartum perineal wound care from a cultural perspective: A qualitative study - Diana Ulfah; Yani Marlina (THE JOURNAL OF Mother and Child Health Concerns, 2026)
Background: Postpartum mothers undergoing vaginal delivery face a significant risk of perineal trauma, a condition with a high global prevalence (2.7 million cases in 2020, with 75% of the incidence in Indonesia) that, if not managed properly, can lead to serious complications such as infection, prolonged pain, and sexual dysfunction, exacerbated by the anatomical reality of persistent exposure to lochia moisture. Effective recovery fundamentally relies on crucial factors including hygiene, nutrition, and early mobilization, yet the role of family support a key determinant in decision-making and practical care remains underexplored, particularly in the highly multicultural context of Indonesia. This cultural perspective is crucial because local traditions and beliefs often introduce dietary or activity taboos that directly impact healing. Therefore, to address the common morbidity associated with perineal wounds and the recorded perineal rupture rate of 54% in regions such as West Java, this qualitative study is urgently needed to address the knowledge gap by in-depth exploring: "How does family support influence perineal wound healing from a cultural perspective?" Purpose: To deeply explore and describe the various forms of family support provided to postpartum mothers for perineal wound care, specifically examining the influence of diverse cultural aspects (cultural variables) within the Indonesian context. This focus on the cultural dimension represents the novelty of this research. Results: From analysis of interview transcripts with participants revealed two main themes describing the dimensions of family support: emotional, instrumental, and informational. Each theme consists of several. Emotional: Providing a sense of security and peace, as well as mental strength within the nuclear family. Instrumental: Providing nutritious food and drinks, managing the household, and caring for the baby. Informational: Information from health workers conveyed by the family, and selectively adapted traditional information.. Conclusion: Family support for perineal care in postpartum mothers, viewed from a cultural perspective, is comprehensive and can be categorized into four distinct themes. These themes highlight how culturally embedded practices and family dynamics significantly influence and enhance mothers' ability to perform appropriate perineal wound care, ultimately promising improved maternal health outcomes.